AP IX, 484 (Palladas): Aiolos serviert Wind - Kondakova, Daria; Kuznetsova, Natalya (Hyperboreus, 2017)
The paper aims to analyse Palladas’ epigram AP 9. 484 and the function of allusions to Homer in it. The speaker gets “a bird full of winds” as a present, which he compares to the bag of winds given to Odysseus by Aeolus. Most commentators think that this bird was simply not stuffed, hence the disappointment; however, the comparison with Aeolus’ bag of winds does not justify this interpretation. A parallel from Aristophanes (Av. 1076–1083), unnoticed by other commentators, shows that ancient merchants used to blow up birds to make them look more appealing to the potential customer, and supports literal understanding, i.e., that the bird in Palladas’ epigram is actually inﬂated. The sender does it himself (γεμίσας), but the reason behind sending this kind of present stays unclear. Although attempts have been made to reconstruct the possible relationship between the sender and the recipient, they prove to be unfounded. An analysis of the expression ἀνεμώλιον ἦτορ concludes the paper. It is argued that the primary meaning of the adjective ἀνεμώλιος, i. e. ‘useless’, ﬁts the context of the epigram in question and it is not needed to look any further. Palladas’ “Aeolus” is useless, as well as his wind-stuffed bird, which sets him in contrast to the real Aeolus from the Odyssey and rounds up the joke.